Analisis Strategi Bersaing Bisnis Guna Mempertahankan Eksistensi Usaha Dalam Menghadapi Maraknya Coffee Shop Yang Ada Di Kota Malang (Studi Kasus Pada Aromatic Coffee And Roastery Malang) - Muhamad Rifki Arifian; Agus Widarko; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractIn the era of globalization, the economic growth of Malang City continues to grow, and various sizes and types of industries have supported the economy of Malang City with all the dynamics that are sustainable, one of which is coffee shop. This research aims to find out the competitive business strategies applied by Aromatic Coffee and Roastery Malang to maintain business existence in the face of the rise of coffee shops in Malang City.In this study, primary data collection was conducted through in-depth interviews to informants in this study, namely Owners, Employees and Customers. While secondary data is obtained through literature studies, research journals, overview of Aromatic Coffee and Roastery Malang. The research method used is a qualitative descriptive analysis method. The analytical methods used are SWOT Analysis, IFE matrix, EFE matrix, and SWOT Matrix.The results of the IFE and EFE matrix show the position of the company quadrant is in Quadrant I. This position shows that profitability is very high, the company has the opportunity and strength to take advantage of existing association opportunities. The recommended strategy is Progressive which means the organization is in ideal and consistent circumstances, and is very likely to continue development, growth, and maximum progress. Keywords: Competing Strategies, SWOT Analysis, Coffee Shop